Pyridoxamine is a substrate of the energy-coupling factor transporter HmpT - Wang, Tingliang (Cell Discov, 2015)
Energy-coupling factor (ECF) transporters belong to a novel family of proteins that forms a subset within the ATP-binding cassette (ABC) transporter family. These proteins are responsible for the uptake of micronutrients in bacteria. ECF transporters are composed of four proteins: the A- and A′-components, the T-component and the S-component. One of the ECF transporters, named HmpT, was crystallized in the apo form with all four components. It is currently unknown whether HmpT serves as a transporter for hydroxymethyl pyrimidine or the different forms of vitamin B6 (pyridoxine, pyridoxal or pyridoxamine). Using a combination of molecular dynamics (MD) simulations and mass spectrometry, we have identified pyridoxamine to be the preferred substrate of HmpT. Mass spectra show that the mass of the substrate from the HmpT–substrate complex matches that of pyridoxamine. MD simulations likewise indicate that pyridoxamine interacts most strongly with most of the conserved residues of the S-component (Glu 41, His 84 and Gln 43) compared with the other vitamin B6 forms. Furthermore, the simulations have implied that loops 1 and 5 of the S-component can participate in the gating action for HmpT.